Ergo - Lean implementation to increase productivity in industrial companies: Systematic Literature Review - MARTINEZ MAQUERA, GIANELA LEIDY; SANTAMARIA TANTAVILCA, LUIGGI ALESSANDRO; FIGUEROA LEON, RUBEN ADRIAN; MELGAREJO ALIAGA, DAVID MARTIN (LACCEI, 2025)
This study explores the combination of Lean Manufacturing with ergonomic practices to improve both productivity and the work environment in the industrial sector. A systematic literature review was conducted following the PRISMA methodology. The search was carried out in the Scopus database using a search equation that combined terms related to Lean and ergonomics. 50 articles were obtained for analysis, after using the inclusion and exclusion criteria carefully applied. The main findings indicate that 62% of the methodologies used are based on Lean Manufacturing and 24% on ergonomic practices. The most commonly used tools include Value Stream Mapping (VSM), REBA, RULA and Kaizen. These practices have been shown to reduce cycle times, improve operational efficiency, and decrease ergonomic risks. The studies highlight that the combination of these methodologies improves both productivity and worker well-being. Furthermore, the integration of both offers significant benefits, although it also poses challenges. The simultaneous implementation of both methodologies is crucial to eliminate waste and improve working conditions. However, a lack of representation of qualitative studies and research in certain industrial sectors was observed. Tools such as VSM and ergonomic assessments are effective in reducing waste and improving occupational health. Additional studies are recommended to validate these findings in various industrial contexts and to further explore the interaction between both methodologies.